Hexose transport in Torulaspora delbrueckii: identification of Igt1, a new dual-affinity transporter - Pacheco, Andreia Sofia Alves Pinto (2020)
Torulaspora delbrueckii is a yeast species receiving increasing attention from the biotechnology industry, with particular relevance in the wine, beer and baking sectors. However, little is known about its sugar transporters and sugar transport capacity, frequently a rate-limiting step of sugar metabolism and efficient fermentation. Actually, only one glucose transporter, Lgt1, has been characterized so far. Here we report the identification and characterization of a second glucose transporter gene, IGT1, located in a cluster, upstream of LGT1 and downstream of two other putative hexose transporters. Functional characterization of IGT1 in a Saccharomyces cerevisiae hxt-null strain revealed that it encodes a transporter able to mediate uptake of glucose, fructose and mannose and established that its affinity, as measured by Km, could be modulated by glucose concentration in the medium. In fact, IGT1-transformed S. cerevisiae hxt-null cells, grown in 0.1% glucose displayed biphasic glucose uptake kinetics with an intermediate- (Km = 6.5 ± 2.0 mM) and a high-affinity (Km = 0.10 ± 0.01 mM) component, whereas cells grown in 2% glucose displayed monophasic kinetics with an intermediate-affinity (Km of 11.5 ± 1.5 mM). This work contributes to a better characterization of glucose transport in T. delbrueckii, with relevant implications for its exploitation in the food industry.